Biomass derived carbon sphere composite material as well as preparation method and application thereof
By developing biomass-derived carbon sphere composite materials, using the cobalt-nitrogen coordination structure to improve catalytic activity, the problems of high cost and insufficient stability of existing precious metal catalysts are solved, and high-efficiency and low-cost dual-function catalysts are realized, suitable for new energy devices.
Patent Information
- Application Number
- CN202411813958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Existing bifunctional catalysts are mainly based on precious metal materials such as platinum (Pt) and iridium (Ir), which limit their large-scale commercial applications due to their high cost, scarcity and insufficient stability during long-term operation.
A biomass-derived carbon sphere composite material is developed, including biomass carbon spheres and cobalt bridged with biomass carbon spheres through nitrogen, which binds to the carbon spheres in the form of chemical bonds to form a cobalt-nitrogen coordination structure, thereby improving catalytic activity.
As a dual-function catalyst, this biomass-derived carbon sphere composite can efficiently catalyze oxygen reduction reaction and oxygen precipitation reaction, have high stability and conductivity, low cost, and is easy to industrial production. It is suitable for new energy devices such as zinc air batteries and fuel cells.
Smart Images

Figure CN119650724A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a biomass-derived carbon ball composite material and a preparation method and application thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly prominent environmental pollution problems caused by traditional fossil fuels, the development of efficient, environmentally friendly and renewable energy conversion and storage technologies has become the focus of current research. New energy devices such as zinc-air batteries, fuel cells and supercapacitors have attracted much attention due to their high energy density and environmental friendliness. The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in electrocatalytic reactions are the key processes in these devices, and their catalyst performance directly affects the efficiency and life of the devices. Therefore, the development of electrocatalysts with dual-functional catalytic activity of ORR and OER has become one of the core issues to improve the performance of energy devices.
[0003] Most of the existing bifunctional catalysts are based on precious metal materials, such as platinum (Pt) and iridium (Ir). Although these catalysts show excellent catalytic activity in ORR and OER, their high cost, scarcity and insufficient stability during long-term operation limit their large-scale commercial application. Therefore, the development of non-precious metal-based, efficient and environmentally friendly bifunctional catalysts has become an urgent technical need. Summary of the invention
[0004] In view of this, the present invention provides a biomass-derived carbon ball composite material and a preparation method and application thereof. The biomass-derived carbon ball composite material provided by the present invention can efficiently catalyze oxygen reduction reaction and oxygen evolution reaction as a bifunctional catalyst, and has a low preparation cost, which is convenient for industrial production.
[0005] In order to solve the above technical problems, the present invention provides a biomass-derived carbon ball composite material, comprising biomass carbon balls and cobalt bridged with the biomass carbon balls by nitrogen, wherein the nitrogen is combined with the biomass carbon balls in the form of chemical bonds.
[0006] Preferably, the biomass-derived carbon ball composite material has a pore structure, the average pore diameter of the pore structure is 2.2 to 2.4 nm, and the specific surface area of the biomass-derived carbon ball composite material is 380 to 400 m 2 / g.
[0007] The present invention also provides a method for preparing the biomass-derived carbon ball composite material described in the above technical solution, comprising the following steps:
[0008] Apples, melamine, soluble cobalt salt and water are mixed and subjected to a hydrothermal reaction, and a solid product after the hydrothermal reaction is calcined to obtain the biomass-derived carbon ball composite material.
[0009] Preferably, the soluble cobalt salt comprises cobalt nitrate or cobalt chloride.
[0010] Preferably, the method further comprises: pre-treating the apples before mixing; the pre-treating comprises the following steps:
[0011] removing sepals and peduncles from the apples and slicing the apples to obtain apple slices;
[0012] The apple slices are dried to obtain dried apples; the moisture content of the dried apples is 8-12 wt %.
[0013] Preferably, the mass ratio of the dried apples to the soluble cobalt salt is 4-7:2-3;
[0014] The mass ratio of the melamine to the soluble cobalt salt is 2-3:2-3.
[0015] Preferably, the temperature of the hydrothermal reaction is 200-220° C., and the time of the hydrothermal reaction is 22-26 hours.
[0016] Preferably, the calcination temperature is 650-750°C, the heating rate to the desired calcination temperature is 4-6°C / min, and the calcination holding time is 1.8-2.2h;
[0017] The calcination is carried out under a protective atmosphere.
[0018] The present invention also provides the use of the biomass-derived carbon sphere composite material described in the above technical solution or the biomass-derived carbon sphere composite material prepared by the preparation method described in the above technical solution as a catalyst.
[0019] Preferably, the catalyst is a bifunctional catalyst that catalyzes oxygen reduction reaction and oxygen evolution reaction.
[0020] The present invention provides a biomass-derived carbon ball composite material, comprising biomass carbon balls and cobalt bridged with the biomass carbon balls by nitrogen, wherein the nitrogen is combined with the biomass carbon balls in the form of chemical bonds; the biomass used to prepare the biomass carbon balls is apple. The present invention uses biomass carbon balls as a matrix, and the biomass carbon balls have a porous structure, a high specific surface area, and good electrical conductivity, which not only have good environmental protection properties but also contribute to the diffusion of reactants and the rapid transfer of intermediates during the electrocatalytic process, significantly improving the overall performance of the catalyst. The present invention further improves the catalytic activity of the biomass carbon balls by doping heterogeneous elements of nitrogen and cobalt on the surface of the biomass carbon balls. The biomass composite material provided by the present invention is a high-efficiency, low-cost bifunctional electrocatalyst that can exhibit excellent performance in oxygen reduction and oxygen evolution reactions, and also has high stability and electrical conductivity, and is suitable for new energy devices such as zinc-air batteries and fuel cells, and has good application prospects.
[0021] The present invention also provides a method for preparing the biomass-derived carbon ball composite material described in the above technical solution, comprising the following steps: mixing apples, melamine, soluble cobalt salts and water and conducting a hydrothermal reaction, and calcining the solid product after the hydrothermal reaction to obtain the biomass-derived carbon ball composite material. Apples are a rich agricultural byproduct with a wide range of sources and low prices. The present invention uses apples as a precursor and prepares a carbon material with a unique spherical structure through a reasonable carbonization process. This type of carbon material has a high specific surface area and a porous structure, which helps to increase the active sites of the catalyst and improve the diffusion efficiency of the reactants in the electrocatalytic process. The present invention further enhances its electrocatalytic performance in oxygen reduction reaction and oxygen evolution reaction by doping heterogeneous element nitrogen and non-precious metal component cobalt through hydrothermal reaction. The present invention prepares a material with catalytic activity in both oxygen reduction and oxygen evolution reactions through a simple method, with low production cost, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of the biomass-derived carbon ball composite material in the embodiment;
[0023] Figure 2 The XRD spectra of the carbon-based materials prepared in Example 1 and Comparative Examples 1 to 2, wherein (a) is the XRD spectra of the biomass-derived carbon sphere composite material prepared in Example 1, and (b) is the XRD spectra of the carbon-based materials prepared in Comparative Examples 1 and 2;
[0024] Figure 3 The XPS spectra of the carbon-based materials prepared in Example 1 and Comparative Examples 1-2;
[0025] Figure 4 The BET graphs of the carbon-based materials prepared in Example 1 and Comparative Examples 1-2, wherein (a) is the BET graph of the biomass-derived carbon sphere composite material prepared in Example 1, (b) is the BET graph of the carbon-based material prepared in Comparative Example 1, and (c) is the BET graph of the carbon material prepared in Comparative Example 2;
[0026] Figure 5 The SEM images of the carbon-based materials prepared in Example 1 and Comparative Examples 1-2 are shown;
[0027] Figure 6 This is a SEM image of the carbon-based material prepared in Comparative Example 3;
[0028] Figure 7 HRTEM image of the biomass-derived carbon sphere composite material prepared in Example 1;
[0029] Figure 8The ORR activity test results of Co@N-AP, N-AP and AP materials, where (a) is the LSV curve of ORR, (b) is the Tafel slope based on the LSV curve, and (c) is the H2O2 yield and the number of electron transfers;
[0030] Fig. 9 The LSV and KL equation curves of Co@N-AP, N-AP and AP at different rotation speeds;
[0031] Fig.10 The LSV test results of Co@N-AP, N-AP and AP, where (a) is the LSV curve of OER, (b) is the Tafel slope based on (a), (c) is the impedance diagram of OER, and (d) is the IT stability test;
[0032] Fig.11 ECSA test results, where (a) is the CV curve of Co@N-AP, (b) is the CV curve of N-AP, (c) is the CV curve of AP, and (d) is the double-layer capacitance of Co@N-AP, N-AP and AP materials;
[0033] Fig.12 The test results of ZABs prepared with Co@N-AP and Pt / Ir / C catalysts as cathode materials, where (a) is the voltage at different current densities, (b) is the open circuit voltage, and (c) is the specific capacity. DETAILED DESCRIPTION
[0034] The invention provides a biomass-derived carbon ball composite material, comprising biomass carbon balls and cobalt bridged with the biomass carbon balls through nitrogen, wherein the nitrogen is combined with the biomass carbon balls in the form of chemical bonds.
[0035] As a specific embodiment of the present invention, the biomass-derived carbon ball composite material has a pore structure, the average pore size of the pore structure can be 2.2 to 2.4, specifically 2.2 nm, 2.3 nm, 2.34658 nm or 2.4 nm, and the specific surface area of the biomass-derived carbon ball composite material can be 380 to 400 m 2 / g, which can be specifically 380m 2 / g, 390m 2 / g, 390.7740m 2 / g or 400m 2 As a specific embodiment of the present invention, the biomass for preparing the biomass carbon balls can be apple.
[0036] The present invention also provides a method for preparing the biomass-derived carbon ball composite material described in the above technical solution, comprising the following steps:
[0037] Apples, melamine, soluble cobalt salt and water are mixed and subjected to a hydrothermal reaction, and a solid product after the hydrothermal reaction is calcined to obtain the biomass-derived carbon ball composite material.
[0038] As a specific embodiment of the present invention, the method may further include: pre-treating the apples before mixing; the pre-treating may include the following steps:
[0039] removing sepals and peduncles from the apples and slicing the apples to obtain apple slices;
[0040] The apple slices are dried to obtain dried apples.
[0041] The present invention has no special requirements for the slicing, and the conventional method in the art can be used. Slicing the apples facilitates the subsequent hydrothermal reaction and calcination. As a specific embodiment of the present invention, the moisture content of the dried apples can be 8-12wt%, and can be specifically 10wt%. As a specific embodiment of the present invention, the drying temperature can be 75-85°C, and can be specifically 75°C, 80°C or 85°C; the drying time can be 22-26h, and can be specifically 22h, 24h or 26h.
[0042] As a specific embodiment of the present invention, the soluble cobalt salt may include cobalt nitrate or cobalt chloride. In the present invention, melamine is used as a nitrogen source, cobalt nitrate is used as a cobalt source, and the material contains only H, C, N, O, and Co, without introducing other redundant elements.
[0043] As a specific embodiment of the present invention, the mass ratio of the dried apples to the soluble cobalt salt can be 4-7:2-3, specifically 2:1, 4:3, 5:2, 5:3, 3:1, 7:2 or 7:3; the mass ratio of melamine to the soluble cobalt salt can be 2-3:2-3, specifically 1:1, 2:3 or 3:2; the water can be deionized water, and the volume ratio of the mass of the dried apples to the water can be 1-2g:10-15mL, specifically 1g:10mL, 1g:12.5mL or 1g:15mL.
[0044] As a specific embodiment of the present invention, the mixing can be carried out under stirring conditions, the stirring can be magnetic stirring, and the time of the magnetic stirring can be 25 to 35 minutes, specifically 25 minutes, 30 minutes or 35 minutes.
[0045] As a specific embodiment of the present invention, the temperature of the hydrothermal reaction can be 200-220°C, specifically 200°C, 210°C or 220°C; the time of the hydrothermal reaction can be 22-26h, specifically 22h, 24h or 26h. As a specific embodiment of the present invention, the hydrothermal reaction can be carried out in a reactor lined with polytetrafluoroethylene.
[0046] In the present invention, under hydrothermal conditions, organic substances in apples are partially carbonized to form a preliminary carbon ball skeleton; because apples contain sugars (such as fructose and glucose) and other organic components, these substances undergo a dehydration condensation reaction at high temperature to form a biomass-derived carbon ball material with a spherical structure, namely, carbon-containing microspheres; melamine may undergo weak hydrogen bonds or electrostatic interactions with the surface of apples and be distributed on the surface of apples, and then under the high temperature conditions of the hydrothermal reaction, melamine decomposes to release nitrogen-containing groups (such as ammonia NH3 and part of CN fragments), and then these nitrogen-containing groups react with the surface of the carbon material, are doped into the carbon skeleton, and chemically bonded with the carbon-containing microspheres; under hydrothermal conditions, cobalt ions in a water-soluble cobalt salt are reduced to generate metallic cobalt (Co), and the reducing substance in the reduction process is H2 generated by hydrolysis or carbon generated by thermal decomposition, and the reduced cobalt can be further combined with nitrogen atoms from the decomposition of melamine to form a cobalt-nitrogen (Co-N) coordination structure to bridge the carbon-containing microspheres. This bridging structure helps to enhance the catalytic activity because it optimizes the electron distribution and provides more catalytically active sites.
[0047] As a specific embodiment of the present invention, the hydrothermal reaction may further include: solid-liquid separation of the system after the hydrothermal reaction, washing and drying the solid obtained by the solid-liquid separation. The present invention has no special requirements for the solid-liquid separation, and the conventional method in the field can be used. As a specific embodiment of the present invention, the washing includes water washing and ethanol washing in sequence; the water used for the water washing can be deionized water, and the ethanol used for the ethanol washing can be anhydrous ethanol. As a specific embodiment of the present invention, the drying temperature can be 60 to 80°C, and can be specifically 60°C, 65°C, 70°C, 75°C or 80°C. The present invention has no special limitation on the drying time, as long as the solvent on the solid surface can be removed.
[0048] As a specific embodiment of the present invention, the calcination temperature can be 650-750°C, specifically 650°C, 700°C or 750°C; the heating rate to the required temperature of the calcination can be 4-6°C / min, specifically 4°C / min, 5°C / min or 6°C / min; the calcination holding time can be 1.8-2.2h, specifically 2h; the calcination can be carried out under a protective atmosphere, and the protective atmosphere can be a nitrogen atmosphere. The present invention can prevent cobalt from being oxidized by calcining under a protective atmosphere.
[0049] The present invention can further optimize the structure, performance and chemical composition of the material after calcination, and provide better properties for its final application (such as electrocatalysis). The specific effects of calcination are: 1. Improving the degree of carbonization and enhancing conductivity: The carbon precursor formed during the hydrothermal treatment may contain some organic matter that is not completely carbonized. High-temperature calcination can completely convert these residual organic matter into graphitized carbon, thereby improving the crystallinity of the material. High-temperature calcination can make the carbon material tend to graphitize and improve the conductivity, thereby helping the material to achieve rapid electron transmission in the electrochemical reaction. 2. Stabilizing the coordination structure of cobalt and nitrogen: The cobalt-nitrogen coordination structure formed during the hydrothermal process is further stabilized at high temperature, optimizing the distribution of cobalt-nitrogen bonds, and improving the utilization rate of electrocatalytic active sites. Calcination can induce crystallization and size optimization of cobalt particles, thereby improving their catalytic performance. 3. Increasing the porosity and specific surface area of the material: There may be residual organic matter or by-products (such as incompletely decomposed melamine) after hydrothermal treatment. High-temperature calcination can purify the surface of the material by decomposing these by-products and expose more active sites. During the high-temperature calcination process, the material may form a microporous or mesoporous structure due to gas release (such as CO2, NH3, etc.), thereby increasing the specific surface area and promoting the diffusion and adsorption of catalytic reactants. 4. Regulating the distribution of cobalt: Calcination can also promote the uniform distribution of cobalt particles on the surface of biomass-derived carbon sphere materials, reduce particle agglomeration, and improve the activity and stability of the catalyst. 5. Improve the thermal stability and cycle stability of the material: Biomass-derived carbon sphere materials that have undergone high-temperature treatment (calcination) have higher thermal stability and can withstand harsh electrochemical reaction conditions (such as high temperature or strong alkaline environment). The material structure after high-temperature calcination is more compact, the active sites are more stable, and the performance is not easily attenuated during long-term electrochemical cycles.
[0050] As a specific embodiment of the present invention, the calcination may further include: cooling the calcined product and then grinding it to obtain the biomass-derived carbon sphere composite material. As a specific embodiment of the present invention, the cooling temperature may be 20-40°C, or 25-30°C.
[0051] Figure 1The present invention is a schematic diagram of the preparation process of a biomass-derived carbon sphere composite material prepared in an embodiment, specifically, apple sepals and apple stalks are removed and sliced, and the dried apples are washed and dried at 80°C for 24 hours to obtain dried apples; melamine is used as a nitrogen source, cobalt nitrate is used as a cobalt source, and the dried apples are stirred and mixed, and a hydrothermal reaction is carried out at 220°C for 24 hours; a solid product generated by the hydrothermal reaction is calcined at 700°C for 2 hours to obtain a biomass-derived carbon sphere composite material.
[0052] The present invention also provides the use of the biomass-derived carbon sphere composite material described in the above technical solution or the biomass-derived carbon sphere composite material prepared by the preparation method described in the above technical solution as a catalyst. As a specific embodiment of the present invention, the catalyst can be a bifunctional catalyst that catalyzes oxygen reduction reaction and oxygen evolution reaction; the catalyst can be used in new energy devices such as zinc-air batteries or fuel cells.
[0053] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] The apples were sliced after the sepals and stalks were removed to obtain apple slices; the apple slices were dried at 80°C for 24 hours to obtain dried apples with a moisture content of 10wt%; 4g dried apples, 2g melamine, 2g cobalt nitrate and 50mL deionized water were mixed under magnetic stirring for 30 minutes and then transferred to a reactor lined with polytetrafluoroethylene for hydrothermal reaction at 220°C for 24 hours; the system was separated from the solid and liquid after the hydrothermal reaction, and the solid obtained by the solid-liquid separation was washed with deionized water and anhydrous ethanol in sequence, the washed product was dried at 70°C, heated to 700°C in a nitrogen atmosphere at a heating rate of 5°C / min, and calcined for 2 hours, cooled to 35°C, and then ground to obtain a biomass-derived carbon ball composite material, recorded as Co@N-AP.
[0056] Comparative Example 1
[0057] A carbon-based material was prepared according to the method of Example 1, except that cobalt nitrate was not added during the mixing process. The obtained carbon-based material was recorded as N-AP.
[0058] Comparative Example 2
[0059] A carbon-based material was prepared according to the method of Example 1, except that cobalt nitrate and melamine were not added during the mixing process, and the obtained carbon-based material was apple-derived biomass charcoal, denoted as AP.
[0060] Comparative Example 3
[0061] A carbon-based material was prepared according to the method of Comparative Example 1, except that the dried apples were replaced with pith wood, and the obtained carbon-based material was pith wood-derived biomass charcoal, denoted as JL.
[0062] The carbon-based materials prepared in Example 1 and Comparative Examples 1-2 were subjected to X-ray diffraction detection to obtain XRD spectra, such as Figure 2 As shown, (a) is the XRD spectrum of the carbon-based composite material prepared in Example 1, and (b) is the XRD spectrum of the carbon-based materials prepared in Comparative Examples 1 and 2. Figure 2 The results show that the diffraction peak of the Co@N-AP catalyst corresponds to the crystal plane of Co (PDF#43-1003), indicating the presence of Co in the carbon-based composite material. The diffraction peaks of AP and N-AP materials correspond to the (002) and (100) crystal planes of graphite carbon. As can be seen from the figure, after doping with N, the (002) peak increases significantly, indicating that the N-AP material has a higher degree of graphitization.
[0063] The carbon-based materials prepared in Example 1 and Comparative Examples 1-2 were subjected to X-ray photoelectron spectroscopy to obtain XPS spectra, such as Figure 3 As shown. XPS characterization further confirmed the elemental composition and valence state of the surface of Co@N-AP, N-AP and AP samples. Figure 3 The C1s XPS spectrum in (a) shows that the CN bonds are reduced after the addition of the cobalt source. Figure 3 The XPS spectrum of N1s in (b) shows that the pyridinic nitrogen content of Co@N-AP has increased significantly. Pyridinic nitrogen has been confirmed to be an active species in the redox reaction (ORR), indicating that the catalytic activity of Co@N-AP will be better than that before the cobalt source is doped. Figure 3 The XPS spectrum of Co 2p in (c) shows that Co@N-AP contains a large amount of Co 0 .
[0064] The carbon-based materials prepared in Example 1 and Comparative Examples 1-2 were subjected to N2 adsorption and desorption measurements to further obtain the specific surface area properties of Co@N-AP, N-AP and AP materials, and the BET diagram was obtained, as shown in FIG. Figure 4 As shown, (a) is the BET graph of the carbon-based composite material prepared in Example 1, (b) is the BET graph of the carbon-based material prepared in Comparative Example 1, and (c) is the BET graph of the carbon material prepared in Comparative Example 2. It can be seen from the figure that Co@N-AP, N-AP and AP materials all have mesoporous structures. The average pore size of Co@N-AP is 2.34658nm, and the specific surface area is 390.7740m 2 / g; the average pore size of N-AP is 2.67372nm, and the specific surface area is 388.1498m2 / g; the average pore size of AP is 3.8690nm, and the specific surface area is 155.4317m 2 / g; Among them, the pore size of Co@N-AP material is the smallest, and Co@N-AP has a larger specific surface area. Catalysts with large specific surface area can provide more active sites, which can promote the transfer of reactants and increase the reaction rate of redox.
[0065] The carbon-based materials prepared in Example 1 and Comparative Examples 1-2 were examined by scanning electron microscopy to obtain SEM images. Figure 5 As shown (the scale bar is 2 μm). Figure 5 It can be seen that after hydrothermal treatment, the dried apples formed the shape of carbon balls, which can enhance the specific surface area of the material. Figure 6 This is a SEM image of the carbon material prepared in Comparative Example 3. Figure 5 and Figure 6 It can be seen that the carbon material prepared after replacing apples with plywood does not have a carbon ball structure, while apples will form a carbon ball structure after a hydrothermal reaction.
[0066] The biomass-derived carbon sphere composite material prepared in Example 1 was subjected to high-resolution transmission electron microscopy to obtain an HRTEM image, as shown in FIG. Figure 7 As shown, (a) is the HRTEM image of Co@N-AP (200nm), (b) is the HRTEM image of Co@N-AP (5nm), (c) is the atomic resolution STEM image of the (111) crystal plane of Co@N-AP, and (d) is the intensity distribution diagram of cobalt (Co). Figure 7 From (a), we can see that Co@N-AP has a large number of carbon sphere structures. The carbon framework is conducive to the diffusion and migration of oxygen species, which helps the catalytic reaction. Figure 7 In (b), it can be seen that the lattice spacing of Co@N-AP is 0.204nm, which corresponds to the crystal plane of Co(111), further confirming the existence of Co nanoparticles. The atomic resolution STEM image of Co@N-AP and the corresponding intensity distribution map of cobalt (Co) can further show the lattice spacing of Co@N-AP.
[0067] Preparation process of catalyst ink: 3 mg of sample and 3 mg of carbon black are evenly mixed, 35 mL of petroleum ether is added, and after ultrasonic treatment for 4 hours, centrifugation is performed and the mixture is placed in an oven at 60°C for thorough drying. Take 6 mg of the dried mixture, add 1470 μL of N,N-dimethylformamide and 30 μL of Nafion-117, and ultrasonic treatment is performed for 6 hours to obtain catalyst ink. After the materials prepared in Example 1 and Comparative Examples 1 to 2 are used as samples to prepare catalyst ink, the ORR activity of Co@N-AP, N-AP and AP materials is evaluated using a standard three-electrode test system to obtain the ORR LSV curve, ORR-Tafel curve, and ORR electron transfer number and intermediate product yield curve, as shown in FIG. Figure 8 As shown, (a) is the LSV curve of ORR, (b) is the Tafel slope based on the LSV curve, and (c) is the H2O2 yield and the number of electron transfers. The specific detection conditions are: 10 μL of catalyst ink is dropped on the glassy carbon electrode (0.071 cm 2 ), and after drying, placed in an electrolyte (1M KOH solution), and the LSV curve was obtained by scanning from the potential range of 0 to 1V at a scanning rate of 2mv / s. Figure 8 In (a), it can be seen that the half-wave potentials of the three catalysts Co@N-AP, N-AP and AP are 0.82V, 0.72V, and 0.80V, respectively. Among them, Co@N-AP exhibits better ORR catalytic performance than the other two materials, close to the level of precious metal Pt / C, confirming that it has relatively excellent ORR activity. In order to further evaluate the ORR performance, the Tafel slope was calculated. Figure 8 (b) shows the Tafel slopes obtained through the LSV curves: Co@N-AP is 78.82mV dec -1 , N-AP is 99.96mV dec -1 , AP is 123.35mV dec -1 Among these materials, Co@N-AP has the smallest Tafel slope, showing higher electron transfer and ORR activity. Figure 8 From (c), it can be seen that the number of electron transfers of Co@N-AP is 4 electron transfers.
[0068] In order to analyze the relationship between the reaction kinetics and active sites of the oxygen evolution reaction (OER) of the catalyst, the C dl The ECSA of the catalysts was evaluated to obtain the LSV of Co@N-AP, N-AP and AP at different rotation speeds and their corresponding KL equations, such as Fig. 9As shown, (a) is the LSV curve of Co@N-AP at different speeds, (b) is the LSV curve of N-AP at different speeds, (c) is the LSV curve of AP at different speeds, (d) is the Koutecky-Levich equation curve of Co@N-AP, (e) is the Koutecky-Levich equation curve of N-AP, and (f) is the Koutecky-Levich equation curve of AP; the detection conditions are in an oxygen-saturated 0.1M KOH solution, and the LSV curves are obtained by testing at different speeds (400-2400rpm, with an interval of 400rpm). Fig. 9 It can be seen that the number of electron transfers in the ORR catalytic process of Co@N-AP is 3.85, which is close to 4 electron transfers.
[0069] In order to evaluate the OER catalytic activity of the catalysts, LSV tests were performed on Co@N-AP, N-AP, and AP. The results are shown in Fig.10 As shown, (a) is the LSV curve of OER; (b) is the Tafel slope based on (a); (c) is the impedance diagram of OER; (d) is the IT stability test result; the detection conditions are to place the catalyst in 1M KOH electrolyte after drying, and obtain the LSV curve by scanning from the potential range of 0 to 1V at a scanning rate of 2mv / s. Fig.10 The Ir / C in (a) and (b) is a result of comparison using carbon loaded with precious metal iridium purchased from Prematek Chuangya Chemical Co., Ltd. Fig.10 In (a), the overpotential of Co@N-AP for OER at j = 10 mA cm-2 is 1.54 V, which shows a relatively small overpotential, indicating that Co@N-AP has excellent OER catalytic activity. The Tafel slope was further analyzed to further explore the OER kinetics. Fig.10 (b) shows the Tafel slopes of each catalyst. From the figure, we can see that the Tafel slopes are: Co@N-AP is 210.6mV dec -1 , N-AP is 413.83mV dec -1 , AP is 418.32mV dec -1 , the smaller Tafel slope displayed by Co@N-AP indicates that it has better OER kinetics and efficient OER catalytic activity. Fig.10 (c) shows the EIS graphs of the three catalysts, showing that Co@N-AP has the smallest semicircle, indicating that it has lower charge transfer resistance and higher conductivity during the OER reaction. Fig.10 (d) is the it stability image of OER, which shows that Co@N-AP has good stability.
[0070] By comparing C dl The ECSA of the catalyst was evaluated and the results were as follows Fig.11 As shown, (a) is the CV curve of Co@N-AP, (b) is the CV curve of N-AP, and (c) is the CV curve of AP; (d) is the double layer capacitance of Co@N-AP, N-AP and AP materials; the detection conditions are in 1M KOH, the ECSA of each catalyst and the corresponding C dl .Depend on Fig.11 It can be seen that Co@N-AP shows a relatively large C dl values, indicating that the catalyst has relatively more exposed active sites and a fast electron transfer process.
[0071] From the above test results, it can be seen that Co@N-AP exhibits relatively excellent bifunctional catalytic performance. Therefore, it is used as the cathode of liquid zinc-air batteries (ZABs), and liquid ZABs based on precious metal Pt / Ir / C (purchased from Prematek Chuangya Chemical Co., Ltd.) are used as the control group for performance evaluation. The results are as follows Fig.12 As shown, (a) is the voltage at different current densities, (b) is the open circuit voltage, and (c) is the specific capacity; the test conditions are that the electrolyte solution is 6MKOH and 0.2M Zn(Ac)2, and the performance parameters of the liquid zinc-air battery are tested by the CHI760E electrochemical workstation and the Blue Battery Test System. Fig.12 From the step diagrams of ZABs prepared with Co@N-AP catalyst and ZABs prepared with noble metal-based catalysts in (a), it can be seen that ZABs based on Co@N-AP catalyst exhibit better voltage than ZABs based on noble metal-based catalysts. Fig.12 (b) is the open circuit voltage. The ZABs based on Co@N-AP catalyst have an open circuit voltage (1.46 V) similar to that of noble metal-based ZABs. Fig.12 (c) shows the specific capacity of liquid ZABs. At different current densities, the liquid ZABs based on Co@N-AP catalyst show regular voltage changes.
[0072] According to the above test results, it can be seen that the application of Co@N-AP as an electrocatalyst in liquid ZABs has good development prospects.
[0073] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A biomass-derived carbon ball composite material, characterized in that: The invention comprises biomass carbon balls and cobalt bridged with the biomass carbon balls by nitrogen, wherein the nitrogen is combined with the biomass carbon balls in the form of chemical bonds.
2. The biomass-derived carbon ball composite material according to claim 1, characterized in that: The biomass-derived carbon ball composite material has a pore structure, the average pore diameter of the pore structure is 2.2-2.4 nm, and the specific surface area of the biomass-derived carbon ball composite material is 380-400 m 2 / g.
3. The method for preparing the biomass-derived carbon ball composite material according to claim 1 or 2, comprising the following steps: Apples, melamine, soluble cobalt salt and water are mixed and subjected to a hydrothermal reaction, and a solid product after the hydrothermal reaction is calcined to obtain the biomass-derived carbon ball composite material.
4. The preparation method according to claim 3, characterized in that: The soluble cobalt salt includes cobalt nitrate or cobalt chloride.
5. The preparation method according to claim 3, characterized in that: The method further includes: pre-treating the apples before mixing; the pre-treating includes the following steps: removing sepals and peduncles from the apples and slicing the apples to obtain apple slices; The apple slices are dried to obtain dried apples; the moisture content of the dried apples is 8-12 wt %.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the dried apples to the soluble cobalt salt is 4-7:2-3; The mass ratio of the melamine to the soluble cobalt salt is 2-3:2-3.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The temperature of the hydrothermal reaction is 200-220° C., and the time of the hydrothermal reaction is 22-26 hours.
8. The preparation method according to any one of claims 3 to 6, characterized in that: The calcination temperature is 650-750°C, the heating rate to the desired calcination temperature is 4-6°C / min, and the calcination holding time is 1.8-2.2h; The calcination is carried out under a protective atmosphere.
9. Use of the biomass-derived carbon sphere composite material according to claim 1 or 2 or the biomass-derived carbon sphere composite material prepared by the preparation method according to any one of claims 3 to 8 as a catalyst.
10. The use according to claim 9, characterized in that: The catalyst is a bifunctional catalyst for catalyzing oxygen reduction reaction and oxygen evolution reaction.